The Load Structure in International Competitive Climbing - Winkler, Marvin; Künzell, Stefan; Augste, Claudia (Frontiers in Sports and Active Living, 2022)
The analysis of the load structure in competitions is essential to develop performance structure models from which sport-specific testing and training protocols can be derived. The aim of this study was to characterize the external load structure of competitive climbing at an international level in the disciplines of speed, bouldering, lead, and Olympic combined based on video recordings of top athletes. In speed, the route was completed by women with a median of 11 moves and by men with 9 moves that required 0.73 and 0.60 s per move, respectively. Bouldering competitions are characterized by various bouts of activity with resting periods in between. Athletes attempted a boulder problem, a median of 3 times in the qualification and semi-final rounds and 4 times in the final round with an average attempt duration of 27.0 s. In lead, the load structure is characterized by an average climbing time of 4:09 min and 4:18 min, 31.6 and 30.0 actions, contact times of 6.4 s and 6.2 s, and reach times of 1.4 s and 1.6 s for women and men, respectively. Olympic combined competitions combine all 3 single disciplines starting with speed followed by bouldering and lead and are characterized by high competition loads, long durations of almost 3 h, and relatively short resting periods in between.